Comparison Effectiveness of Epidural Catheter by using Two Techniques Air Versus Saline as Pre-emptive Analgesia in Obstetric Patients - Shaza Khan, Huma Batool, Zeenat Umar (Pakistan Journal of Medical & Health Sciences, 2024)
Background: In obstetric patients, epidural anaesthesia (EA) and combined spinal epidural anaesthesia (CSEA) is commonly preferred techniques due to their efficacy and acceptable safety profile with minimal adverse effects. Objective: To evaluate and compare the efficacy of epidural catheterization techniques involving the use of air versus saline for pre-emptive analgesia in obstetric patients. Methodology: A prospective study was conducted at the Department of Gynecology and Obstetrics of the Hospital from January 2023 to July 2023. A total of 132 patients over 18 years and younger than 38 years undergoing vaginal deliveries were selected. Patients were consecutively allocated into two distinct groups, namely Group A (LOR with air) and Group B (LOR with saline). Results: Nine patients in Group A suffered from hypotension (13.6%) and 13 patients in Group B suffered from hypotension (19.7%). Two patients in Group A developed a dural puncture and 5 patients in Group B had a dural puncture. Three patients in Group A developed PDPH and 2 patients in Group B developed PDPH which was managed conservatively. There is no significant difference in both groups regarding procedural complications. Conclusion: Epidural catheterization via loss of resistance with air (ALOR) and loss of resistance with saline (SLOR) for providing preemptive analgesia in obstetric patients show comparable analgesic effects in terms of efficacy and complications with different success rate of epidural catheter placement which was higher in the ALOR group. Keywords: Anesthesia, Catheter, Epidural, Pregnancy.